Using Gather for counselling & peer support: the anonymous outreach project / Muhammad Aiman Abdul Halim and Noor Azli Affendy Lee - Abdul Halim, Muhammad Aiman; Affendy Lee, Noor Azli (Academy of Language Studies, 2023)
The English Language Club of Universiti Cawangan Pulau Pinang (UiTMCPP) in collaboration with the Counselling and Career Unit and Peer Counsellor UiTMCPP Club conducted a project named Anonymous Outreach from October 2022 to January 2023. This initiative aimed to provide a virtual platform for students who face mental health issues to share and discuss their situations anonymously. Eight students from the organizing committee helped to develop an open-to-all and free-to- access platform using Gather, an interactive video chat platform where each user acts as a playable character in a virtual world. The project aimed to tackle the stigma surrounding mental health in our Malaysian and university community while creating a safe space where students could comfortably talk about their mental health issues. The student developers customized the platform to meet the needs of the project. Several unique rooms or sections were filled with infographics and facts about mental health care and awareness for participants to explore, such as a counseling room to meet up with UiTMCPP counselors, gaming areas, discussion and support section, and many more. The developers only took two months to customize the platform in line with the project's objectives. In November 2022, the platform underwent a three-day trial run or beta testing phase, which involved 30 students from the Permatang Pauh and Bertam campuses, as well as members of the Peer Counsellor Club. A total of 10 participants were involved per session. Based on feedback from beta testers, the student developers continued to modify the platform.